Effect of anti-adhesion agents on cytokine profile in an experimental model of postoperative intra-abdominal adhesions - F.T. Akhmedov; H.B. Isayev; S.V. Guliyeva (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2023)
Many attempts have been made to prevent peritoneal adhesions using anti-adhesion agents, barriers and other therapeutic approaches, but their efficacy has not been widely accepted. Purpose - to determine the effects of mezogel, a mixture of metronidazole, dextran, and contrykal enriched with oxygen based on the pro- and anti-inflammatory cytokine concentration in rats with simulated postoperative peritoneal adhesions. Materials and methods. A total of 90 outbred white rats, divided into three groups of 30 animals each, underwent laparotomy and mechanical injury of the small bowel wall until a drop of blood appeared. After mechanical injury of the small bowel wall, the abdominal wound in group 1 animals (control) was closed with a layered suture technique; group 2 animals (comparison) were administered one mL of mezogel into the abdominal cavity before layer-by-layer suturing; group 3 animals (experimental) were introduced one mL of a specially prepared mixture of metronidazole, dextran, and contrykal (in a ratio of 1:1:0.1, respectively) enriched with oxygen into the abdominal cavity before the laparotomy wound was closed. Each surgical intervention lasted 15-20 minutes. On days 5, 10 and 21 of the experiment interleukin (IL) 4, IL-6, IL-10 and tumour necrosis factor alpha (TNF-α) were determined in the blood by enzyme immunoassay using corresponding test kits manufactured by Bender Medsystems (Austria). Results. The levels of the anti-inflammatory cytokines IL-4 and IL-10 increased dynamically in groups 2 and 3, while group 1 showed their decrease. The proinflammatory cytokine IL-6 and TNF-α concentration decreased in the experimental and comparison groups during the study period. On day 5 in groups 2 and 3, compared to group 1, the IL-6 concentration was reduced by 28.4% (p=0.029) and 41.0% (p=0.006), respectively. Group 3 animals had a 17.6% (p=0.043) lower IL-6 level compared to group 2 animals. On days 10 and 21 a dynamic decrease in IL-6 was observed in the animals of groups 2 and 3. Group 3 animals had the lowest TNF-α, 41.9 % (p=0.001) lower than in group 1, and 31.7 % (p=0.118) lower than in group 2. There were significant strong relationships detected between IL-10 and IL-6 in all groups on day 5 of the study. Conclusions. The administration of anti-adhesion agents, mezogel and an oxygen-enriched mixture of metronidazole, dextran, and contrykal, inhibits inflammation, which is expressed as a decrease in the concentrations of IL-6 and TNF-α. These agents lead to a negative interaction of anti-inflammatory cytokines with pro-inflammatory cytokines, in particular IL-4 with IL-6 and IL-10 with IL-6, indicating a greater prophylactic effect. The experiments with laboratory animals were provided in accordance with all bioethical norms and guidelines. No conflict of interests was declared by the authors.